Soil productivity from the sandy pampas region under the present agricultural conditions - Díaz Zorita, Martín (2012)
Fil: Díaz Zorita, Martín. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones en Biociencias Agrícolas y Ambientales (INBA). Buenos Aires, Argentina.